Alternative cost-effective media to facilitate MODS culture for diagnostics of tuberculosis - Sheen, Patricia (2022)
Most culture-based methods for tuberculosis diagnosis remain low-cost options for low- and mid-income countries. The MODS culture is a rapid and low-cost assay to diagnose tuberculosis and determine drug susceptibility. However, its implementation is limited due to the low accessibility to supplies required for the enriched medium. In this study, we evaluate two alternative culture media: A powder-based mixed (PM) and a lyophilized media (LM). Catalase, PANTA, and gamma irradiation were evaluated as additions to PM and LM. The culture performance of the alternative media was compared with the standard MODS medium (MM) using Mycobacterium tuberculosis isolates and positive acid-fast smear sputum samples. Overall, no significant difference was observed in the bacterial growth between PM and LM with MM. However, PANTA and gamma irradiation combined reduced bacterial growth significantly in all media variants. A median positivity day of 6 ± 5 days was observed for sputum samples, regardless of the culture medium. The preliminary results show that the two variants culture media have a similar performance to the standard MODS medium. The powder-based media with PANTA (PM_P) showed a time-to-positivity and sensitivity similar to the standard MODS medium. It is the simplest to prepare and does not require any sterilization process.